Design and optimization of mucoadhesive nasal in situ gel containing sodium cromoglycate using factorial design - Shah, Riten A; Mehta, Maulik R; Patel, Dasharath M; Patel, Chhagan N (Asian Journal of Pharmaceutics (AJP), 2014)
Nasal in situ gel of sodium cromoglycate was prepared for sustained release and improvement of drug bioavailability. Carbopol 940 was used as a key ingredient which gives pH-induced sol to gel conversion of the formulations. Different formulations were prepared by varying the concentrations of carbopol 940 and different grades of Hydroxyl Propyl Methyl Cellulose (HPMC K100, HPMC K4M and HPMC K15M). These formulations were evaluated for parameters like pH, drug content, viscosity, gel strength, in vitro drug release and drug excipient compatibility. In this study, the release profile depends on the concentration of carbopol 940 and grade HPMC. A 32 factorial was applied to check the effect of varying the concentration of carbopol 940 (X1) and different grades of HPMC (X2) on the dependent variable i.e. viscosity, mucoadhesive strength, cumulative percentage drug released in 1 h (Q1), 4 h (Q4) and 8 h (Q8) as dependent variables. In vitro release data was fitted to various models to ascertain the kinetic of drug release. Regression analysis and analysis of variance were performed for dependent variables.The results of the F-statistics were used to select the most appropriate model. Formulation F6 was considered optimum which contained carbopol 940 (0.75%) and HPMC K4M (0.50%) and was more similar to the theoretical predicted dissolution profile (f2=70.99). The studies indicate that the formulation was effective in providing in vitro release, in vitro permeation of drug and the mucoadhesion which increases the residence time of drug.